A parallel dipole line system - Gunawan, Oki (2015)
We present a study of a parallel linear distribution of dipole system, which can be realized using a pair of cylindrical diametric magnets and yields several interesting properties and applications. The system serves as a trap for cylindrical diamagnetic object, produces a fascinating one-dimensional camelback potential profile at its center plane, yields a technique for measuring magnetic susceptibility of the trapped object and serves as an ideal system to implement highly sensitive Hall measurement utilizing rotating magnetic field and lock-in detection. The latter application enables extraction of low carrier mobility in several materials of high interest such as the world-record-quality, earth abundant kesterite solar cell, and helps elucidate its fundamental performance limitation.